(untitled) (CIPEEX, 2025)
Introduction: Workers in the industrial sector are subjected to various conditions that reduce cardiovascular health and quality of life. Objective: To associate the type of job function with the cardiovascular health and quality of life of industrial sector workers. Methods: Workers were stratified according to collar type (white: administration and blue: manual labor). CVH was assessed and classified based on the American Heart Association (AHA)’s Life’s Essential 8 (LE8) and quality of life was measured by the SF-36 questionnaire. Results: 82 industrial sector workers were evaluated. The results showed that white-collar workers perform more vigorous physical activities (∆= +86.78 min/week, p=0.003), have lower non-HDL cholesterol levels (∆= -20 mg/dL, p=0.036) and better blood pressure (∆= -8mmHg, p= 0.039). However, they report more physical limitations ((∆= -14.49%, p=0.03). There was an association between collar type and diet (p=0.026), nicotine exposure (p=0.007) and non-HDL cholesterol (p=0.040). Conclusion: White-collar workers had better CVH but reduced quality in limitations due to physical aspects. Thus, the encouragement of healthy eating, physical activity practice, and smoking reduction is suggested.